Frequency of anatomical variation of the sacroiliac joint in asymptomatic young adults and its relationship with sacroiliac joint degeneration. Issue 6 (6th January 2020) - Tok Umay, Sermin; Korkmaz, Mehmet
Abstract: Introduction: To evaluate the variations of the sacroiliac joint (SIJ) in asymptomatic young adults and their relationship to SIJ degeneration. Materials and Methods: A total of 860 SIJs were retrospectively evaluated in 430 abdominal computed tomographies (CT) of abdominal pain cases. The study population consisted of 430 patients (176 female, 254 male) aged 20–45 years with abdominal pain. The anatomical variations of the SIJ were classified as (1) accessory sacroiliac joint, (2) iliosacral complex, (3) bipartite iliac bony plate, (4) semicircular defects, (5) crescent‐like iliac bony plate, and (6) ossification center. The CT findings of SIJ degeneration included joint space narrowing, sclerosis, subcortical cysts, vacuum phenomenon, and osteophytes. Chi‐square and cross tabulation tests were used for statistical analysis. Results: The iliosacral complex was the most common (bilateral) anatomical variation (7.7%, n = 66). A total of 71 SIJ degenerations were detected in cases with anatomical variations. They were determined in 22 (2.6%) iliosacral complex, 19 (2.2%) bipartite iliac bony plate, 15 (1.7%) accessory sacroiliac joint, 6 (0.7%) semicircular defect, 5 (0.6%) crescent‐like iliac bony plate, and 4 (0.5%) ossification center cases. Conclusion: We found that iliosacral complex was the most common SIJ variation in asymptomatic young adults and also that there was significantly more SIJ degeneration among subjects with anatomical variations of the SIJ than those without. SIJ degeneration was most common in subjects with the iliosacral complex variation.